Food Safety Education for Processing and Marketing Groups (Poklahsar) in East Lombok Regency - Aini, Muslihuddin; Hurul'in, Ruhma Ruksalana (Marine Kreatif, 2024)
Food safety is a crucial aspect that must be considered in the production of processed foods to ensure the quality and health of products consumed by the public. East Lombok Regency has several Fish Processing and Marketing Groups (Poklahsar) that require capacity building through food safety training. This activity aims to provide understanding and skills to Poklahsar in three coastal villages, namely Sugian Village, Labuhan Haji Village, and Tanjung Luar Village, regarding good food safety practices. Through pre-test stages, material delivery, and post-test, this training is expected to enhance participants' knowledge of food safety and assist them in obtaining the necessary certification for product legality. The results of the activity showed an increase in participants' understanding of food safety, which is an essential prerequisite for obtaining a Home Industry Food Production (PIRT) permit. This legality will support the broader market reach of Poklahsar products, both locally and nationally.